1994
DOI: 10.1128/cmr.7.4.505
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C: progress and problems

Abstract: The hepatitis C virus (HCV), a single-stranded RNA virus, is the major cause of posttransfusion hepatitis. HCV isolates differ in nucleotide and amino acid sequences. Nucleotide changes are concentrated in hypervariable regions and may be related to immune selection. In most immunocompetent persons, HCV infection is diagnosed serologically, using antigens from conserved regions. Amplification of RNA may be necessary to detect infection in immunosuppressed patients. Transmission by known parenteral routes is fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
55
1
13

Year Published

1997
1997
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 153 publications
(74 citation statements)
references
References 443 publications
(434 reference statements)
3
55
1
13
Order By: Relevance
“…We rate of chronicity after HCV infection, with at least 70% of concluded that HCV structural proteins are not directly those infected developing chronic liver disease. 11 In addition cytopathic in this animal model. (HEPATOLOGY 1997;25: to the morbidity and mortality caused by chronic liver dys-1014-1021.)…”
Section: Those Cells At Six Months Of Age the Livers Of Allmentioning
confidence: 86%
“…We rate of chronicity after HCV infection, with at least 70% of concluded that HCV structural proteins are not directly those infected developing chronic liver disease. 11 In addition cytopathic in this animal model. (HEPATOLOGY 1997;25: to the morbidity and mortality caused by chronic liver dys-1014-1021.)…”
Section: Those Cells At Six Months Of Age the Livers Of Allmentioning
confidence: 86%
“…[1][2][3] Infection with HCV usually results in chronic active hepatitis, which may progress to cirrhosis. Currently, end-stage liver disease resulting from chronic HCV infection is a major reason for referral of patients for orthotopic liver transplantation in the United States.…”
mentioning
confidence: 99%
“…6,7 Although the reasons responsible for relapse are unclear, variables such as length of treatment, HCV genotype, and histological evidence of inflammation and fibrosis at the start of therapy appear to correlate with treatment outcomes. 3,[8][9][10][11] Reverse-transcription (RT) polymerase chain reaction (PCR) techniques to detect HCV RNA during interferon therapy have been widely employed and are considered to be important for optimum management. 12,13 A high level of HCV RNA in serum before treatment is a poor prognostic sign for sustained response; unfortunately, clearance of virus from serum or plasma at the end of treatment as determined by qualitative RT-PCR test does not reliably predict a sustained response.…”
mentioning
confidence: 99%
“…El virus de la hepatitis C (HCV) está cdmpuesto ensayos diagnósticos para la detección de por un genoma de ARN de cadena simple con anticuerpos a estevirus (3)(4)(5)(6). Sin embargo, se ha .sentido positivo de aproximadamente 9.500 observado que las zonas cercanas a la región nucleótidos 19.4 kilobases\.…”
unclassified
“…La proteína estructural del núcleo (C) está altamente conservada y presenta una gran antigenicidad entre los diferentes aislamientos, de ahí la importancia de su incorporación en los Correspondencia: iqpeptidos@cie.sld.cu Recibido: 12/04/00; aceptado: 02/02/01 (3)(4)(5)(6).…”
unclassified